POLITIK HUKUM DALAM PERUMUSAN KALENDER ISLAM (Studi Tentang Kebijakan Kalender Nabi Muhammad SAW di Jazirah Arab dan Kalender Sultan Agung di Tanah Jawa) - Musonnif, Ahmad (Ahkam: Jurnal Hukum Islam, 2016)
Calendar constitutes an important element of a ruler’s policy to control the people and to lead to the achievement of the ruler’s political agenda. The Prophet Mohamed, as a ruler of society, also utilizes the calendar to achieve his main mission to make the society worship to one God (Tauhid). In the case of Javanese Ruler, Sultan Agung, he utilizes the Javanese calendar to maintain the Islamic-Javanese syncretism teaching. Kata kunci: Politik Hukum, Kalender Islam, Kalender Sultan Agung